Contribution of Disulfide Bridges to the Thermostability of a Type A Feruloyl Esterase from Aspergillus usamii. - Xin Yin; Die Hu; Jian-Fang Li; Yao He; Tian-Di Zhu; Min-Chen Wu (PLoS ONE, 2015)
The contribution of disulfide bridges to the thermostability of a type A feruloyl esterase (AuFaeA) from Aspergillus usamii E001 was studied by introducing an extra disulfide bridge or eliminating a native one from the enzyme. MODIP and DbD, two computational tools that can predict the possible disulfide bridges in proteins for thermostability improvement, and molecular dynamics (MD) simulations were used to design the extra disulfide bridge. One residue pair A126-N152 was chosen, and the respective amino acid residues were mutated to cysteine. The wild-type AuFaeA and its variants were expressed in Pichia pastoris GS115. The temperature optimum of the recombinant (re-) AuFaeAA126C-N152C was increased by 6°C compared to that of re-AuFaeA. The thermal inactivation half-lives of re-AuFaeAA126C-N152C at 55 and 60°C were 188 and 40 min, which were 12.5- and 10-folds longer than those of re-AuFaeA. The catalytic efficiency (kcat/Km) of re-AuFaeAA126C-N152C was similar to that of re-AuFaeA. Additionally, after elimination of each native disulfide bridge in AuFaeA, a great decrease in expression level and at least 10°C decrease in thermal stability of recombinant AuEaeA variants were also observed.